Kinking-induced structural evolution of metal oxide nanowires into single-crystalline nanorings - Yan, Chaoyi (2012)
We report an innovative method to fabricate single-crystalline nanorings based on the conventional vapor−liquid−solid (VLS) mechanism. The controllable formation of kinks in functional oxide nanowires (NWs) can be employed to fold the VLS-grown NWs into closed ring-shaped nanostructures. Successful syntheses of single-crystalline In2O3 and Zn2GeO4 nanorings were demonstrated. The present work provides an efficient method for nanoring fabrication based on NWs. The functional metal oxide nanomaterials with unique ring-shaped structures are expected to find interesting applications such as wave-guiding and photonic circuits.